New trends in animation and visualization - Magnenat-Thalmann, Nadia 1946-; Thalmann, Daniel (John Wiley & Sons, 1991)
This selection of works on advanced computer graphics techniques in animation and visualization contains contributions by leading international experts in the field from the U.S., Europe, and Japan presenting new and important topics from a practical and a theoretical viewpoint. It covers virtual environments, object-oriented programming in computer animation, shape interrogation, facial animation, animation in architecture, and human modeling in visualization.